Effects of the Uniform 5% Tariff on Manufacturing - Virginia S. Pineda (Philippine Institute for Development Studies (PIDS), 1997)
Given that the 5% uniform tariff rate by 2004 will be implemented, this study lends support to the substantial benefits to be reaped from it in the form of greater import competition, improved efficiency and better resource allocation. This also identifies the industries heavily favored by its implementation and the industries which it renders vulnerable. Based on the results, suggestions regarding other measures on the improvement of the firm?s ability to compete are offered.
Keywords: 330; liberalization; uniform tariff rate; vulnerability; devaluation